Numerical simulation of pipeline crack detection probe with poly-magnetic structure. Issue 1 (1st December 2022) - Xin, Jiaxing; Zhang, Weiwen; Lu, Run-kun; Chen, Jinzhong; Zhu, Hongwu; He, Renyang
Abstract : The detection and characterization of cracks is one of the key issues in oil and gas transmission pipeline inspection. The weak degree of spatial magnetic field distortion caused by the small size of the crack creates great difficulties for signal extraction. In this paper, we propose an ACM crack detection probe with poly-magnetic structure, and investigate the influence of the core, shield on the detection signal through numerical simulations. The results show that the crack detection probe with the core and shield can effectively improve the distorted magnetic field component in space acquired by the magnetic element, increasing the distorted magnetic field signals in the vertical and horizontal directions by a factor of 2.10 and 1.76 respectively. Verification that ACM probe with poly-magnetic structure can effectively increases the crack-induced magnetic field distortion signal and reduce the probability of misses.